Coexistence of rhcp and fcc phases in hard-sphere colloidal crystals - Dolbnya, I; Petukhov, A; Aarts, D; Vroege, G; Lekkerkerker, H (2005)
We present results for high-resolution small-angle single-crystal X-ray diffraction of hard-sphere silica colloidal crystals. Our results indicate that the stacking probability a of finding an fee stacking sequence in a strongly compressed sample can only have two discrete values of either 0.5 (for rhcp) or 1 (for fcc) in contrast to previous observations on more dilute systems that metastable hard-sphere rhcp crystals may have various values of α. This suggests that, in a concentrated sample, the transition from rhcp to fee does not go by a smooth variation of α, but through a rearrangement mechanism via melting, which leads to the formation of perfect fee crystallites. These crystallites do not possess a single stacking fault as evidenced by the absence of twin fcc reflections. © EDP Sciences.